Alteration of the Mitochondrial Effects of Ceria Nanoparticles by Gold: An Approach for the Mitochondrial Modulation of Cells Based on Nanomedicine - Patricia Gutiérrez-Carcedo; Sergio Navalón; Rafael Simó; Xavier Setoain; Carolina Aparicio-Gómez; Ibane Abasolo; Victor Manuel Victor; Hermenegildo García; José Raúl Herance (Nanomaterials, 2020)
Ceria nanoparticles are cell compatible antioxidants whose activity can be enhanced by gold deposition and by surface functionalization with positive triphenylphosphonium units to selectively target the mitochondria. The antioxidant properties of these nanoparticles can serve as the basis of a new strategy for the treatment of several disorders exhibiting oxidative stress, such as cancer, diabetes or Alzheimer’s disease. However, all of these pathologies require a specific antioxidant according with their mechanism to remove oxidant species excess in cells and diminish their effect on mitochondrial function. The mechanism through which ceria nanoparticles neutralize oxidative stress and their effect on mitochondrial function have not been characterized yet. In the present study, the mitochondria antioxidant effect of ceria and ceria-supported gold nanoparticles, with or without triphenylphosphonium functionalization, was assessed in HeLa cells. The effect caused by ceria nanoparticles on mitochondria function in terms of mitochondrial membrane potential (∆Ψm), adenosine triphosphate (ATP) production, nuclear respiratory factor 1 (NRF1) and nuclear factor erythroid–2–like 1 (NFE2L1) was reversed by the presence of gold. Furthermore, this effect was enhanced when nanoparticles were functionalized with triphenylphosphonium. Our study illustrates how the mitochondrial antioxidant effect induced by ceria nanoparticles can be modulated by the presence of gold.